Diversity of Butterflies on Rajaram College Campus, Kolhapur, Maharashtra, India - Chavan, J. A.; Sutar, P. K.; Sutar, S. S. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
The present study was carried out to understand the butterfly diversity and abundance in Rajaram College, Campus from November 2022 to March 2023 and November 2023 to March 2024. A total 28 species of butterflies belonging to 24 genera and four families were recorded from the present study. From the observed butterflies, the family Nymphalidae was the most dominant among the four families with 14 species, followed by Lycaenidae (07), Papilionidae (04) and Pieridae (03). The present study added valuable information on the diversity of butterfly fauna and will contribute to developing effective conservation.